Crowdsourcing and its relationship to crisis management from the perspective of workers in City for soft drink company - Mohammaed Abed Eshtiwiey, (Technium Social Sciences Journal, 2020)
The study aims at indicating the relation between the crowd sourcing and crisis management from the perspective of the employees in the city soft drinks company in Gaza Strip, where the study community represents all 60 workers in the company. A simple random sample of "40" agents was selected, using a comprehensive survey method. The study followed the analytical descriptive approach, based on the identification of a data collection tool, and concluded a number of findings, the most important of which were: A positive correlation between crowd sourcing and crisis management in the company, and it was found that the company was doing crowdsourcing with a high relative weight of 85.06%. It was found that collaboration with the public was very high (86.64%), communication with the public and information gathering was very high (86.42%), and the company's ability to classify information with a very high relative weight of (84.83%), Its ability to choose alternatives was high (82.08%), and the company's ability to manage crises with a high relative weight (83.73%). The results also showed that there were no statistically significant differences in the sample's responses to the relationship of collective counting dimensions, "communication and information gathering from the public, selection of alternatives" to "crisis management, but age-varying dimensions" classification of information, and collaboration with the public, the overall degree of crowd sourcing" was in favor of age (From 20–less than 35), the study also recommended that a behavioral information portfolio be found to monitor the marketing behavior of the public toward the business of the company. And to provide a firm’s crisis management department or committee to leverage the crowd outsourcing of expected crises effectively.